The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjopen-2018-021580
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of the status of coronary risk biomarkers among Negritos with metabolic syndrome in the east coast of Malaysia

Abstract: ObjectivesTo determine the prevalence of metabolic syndrome (MS), ascertain the status of coronary risk biomarkers and establish the independent predictors of these biomarkers among the Negritos.SettingsHealth screening programme conducted in three inland settlements in the east coast of Malaysia and Peninsular Malaysia.Subjects150 Negritos who were still living in three inland settlements in the east coast of Malaysia and 1227 Malays in Peninsular Malaysia. These subjects were then categorised into MS and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
(43 reference statements)
1
7
1
Order By: Relevance
“…Our more in-depth study reflected similar findings where Jehai had the lowest prevalence of general obesity but had twice the prevalence of dyslipidaemia and apparent risk for cardiovascular diseases compared to Temiar. However, studies suggest that Negritos, of which Jehai is a subgroup, may present with increased coronary risk and inflammatory biomarkers, yet had low pro-thrombosis and endothelial activation (Mokhtar et al, 2016;Mokhsin et al, 2018). These studies suggested that genetic factors may have resulted in lower HDL levels among Negritos, which was also observed in this current study.…”
Section: Discussionsupporting
confidence: 71%
“…Our more in-depth study reflected similar findings where Jehai had the lowest prevalence of general obesity but had twice the prevalence of dyslipidaemia and apparent risk for cardiovascular diseases compared to Temiar. However, studies suggest that Negritos, of which Jehai is a subgroup, may present with increased coronary risk and inflammatory biomarkers, yet had low pro-thrombosis and endothelial activation (Mokhtar et al, 2016;Mokhsin et al, 2018). These studies suggested that genetic factors may have resulted in lower HDL levels among Negritos, which was also observed in this current study.…”
Section: Discussionsupporting
confidence: 71%
“…[38] Among Negritos, Batek, and Jehai HGs from Peninsular Malaysia who receive significant government support and have stable livelihoods demonstrated a much higher (>40%) prevalence of hypertension than our study population. [39,40] The differences in hypertension prevalence observed across these populations might be due to various variables. Aside from genetic, ethnic, and environmental variations, lifestyle, diet, level of physical activity, behavioral risks, and degree of acculturation should all be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Both purposive and snowball sampling approaches are non-random sampling methods that may have limitations but generally used in Orang Asli research. 8,29 The present study provides a community-based picture of the KAP on lifestyle-related NCDs among Orang Asli people in Jelebu, Negeri Sembilan. Poverty and underdevelopment are the predominant features of Orang Asli communities, and education levels still lagging compared to other communities.…”
Section: Correlation Between Knowledge Attitude and Practices Regarding Lifestyle-related Ncdsmentioning
confidence: 94%